Chemical effects on the tribological behavior during copper chemical mechanical planarization - Li, Jing; Liu, Yuhong; Wang, Tongqing; Lu, Xinchun (Materials chemistry and physics, 2015)
Copper chemical mechanical polishing/planarization (CMP) is subject to mechanical actions by abrasive wear coupled with simultaneous chemical effects via slurries at the wafer/pad interface. Therefore, it is necessary to investigate slurry chemical effects on the contact interface. The chemical roles of friction as functions of slurry pH during copper CMP process were studied. The wettability and particle size of the slurry had non-dominant influence on the friction force of the polishing interface. According to OCP measurements, XPS and Raman analysis, chemical reactions occurring on the polishing interface led to varying the tribology behavior during CMP process. The formation of Cu-BTA complex under acidic conditions increased the coefficients of friction (COF), while chemical dissolution under alkaline conditions resulted in lower COF. The results provide more understanding of tribological principles and further optimization of the CMP process. •Chemical roles of friction as functions of slurry pH during CMP are investigated.•The formation of Cu-BTA complex under acidic conditions increased COF.•Chemical dissolution under alkaline conditions resulted in lower COF.